CSIG-26. HETEROGENEITY OF EGFRvIII-POSITIVE GLIOBLASTOMA STEM CELLS: IMPLICATIONS FOR PERSONALIZED DRUG DEVELOPMENT. Issue 11 (6th November 2017) - Kwatra, Madan; Nanni, Cory; Roberts, Callie; Kwatra, Shawn; Lesser, Glenn J; Gilbert, Mark R
Abstract: EGFRvIII, a constitutively active mutant of EGFR, is present in over 20% of glioblastoma patients. To develop pre-clinical models for developing therapies against EGFRvIII-expressing GBMs, we isolated four different EGFRvIII-positive (EGFRvIII+) glioblastoma stem cell lines (GSCs). Molecular characterization of these GSCs revealed that they express different levels of several genes (such as CD133, OLIG2, SOX2, NOTCH1, and transferrin receptor) that are considered as stem cell markers. These molecular differences (or heterogeneity) between EGFRvIII+ GSCs are likely to result in a differential response of these cells to drugs. Additionally, we have identified an EGFRvIII+ GSC line that lacks the wild-type EGFR (wtEGFR) i.e. EGFRvIII+/wtEGFR-. This is a novel finding because it is believed that GBMs that express EGFRvIII also co-express the wtEGFR. In fact, it was shown recently that EGFRvIII activation in GBM is caused by its phosphorylation by the wtEGFR. To begin to understand how EGFRvIII is activated in the setting of GSCs that lack wtEGFR, we used reverse phase protein arrays to compare proteomic profiles of EGFRvIII+/wtEGFR- and EGFRvIII+/wtEGFR+ GSCs. Of the 301 proteins and phosphoproteins examined, sixteen proteins showed significantly different expression. These sixteen proteins are known mediators of EGFR-signaling. Thus, we have shown that EGFR signaling in EGFRvIII+ /wtEGFR+ and EGFRvIII+/wtEGFR- GSCs differs. These difference in EGFR signaling between the two sets of GSCs are likely to result in a differential response to anti-EGFR drugs. Thus, future clinical studies targeting EGFRvIII with EGFR-tyrosine kinase inhibitors would be strengthened by further stratifying EGFRvIII-positive GBM patients.